Sea Level Anomaly Variability Due to Global Climate in the Western Waters of Sumatra - Banjarnahor, Samuel Kristian Alfredo; Silaban, Angeli; Verojenases, Fascal; Irkhos, Irkhos; Lizalidiawati, Lizalidiawati (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
The western waters of Sumatra are part of the Indonesian waters that directly interact with the Indian Ocean, which is a climatologically complex area due to influenced by various atmospheric and marine phenomena that are seasonal and inter annual. Therefore, the purpose of this study is to analyze the influence of the El Niño Southern Oscillation (ENSO) phenomenon on changes in sea level in Western Sumatra waters during the period of 1997-2023. The data used include sea level anomaly (SLA), Oceanic Niño Index (ONI), and Dipole Mode Index (DMI). The results show that strong El Niño, such as in 1997/1998, cause sea level to drop to - 0.3 meters due to intense upwelling. In contrast, El Niño 2015/2016 increased sea level by + 0.2 meters due to the dominance of down welling. During the La Niña period, sea level rose significantly, reaching 0.3 meters in 2022/23. The long-term trend shows an average sea level rise of 0.056-0.064 meters over the last 26 years, with different variations between regions.